Functional connectivity and mild behavioral impairment in dementia‐free elderly - Maryam Ghahremani; Santhosh Nathan; Eric E. Smith; Alexander McGirr; Bradley Goodyear; Zahinoor Ismail (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2023)
Abstract Background Mild behavioral impairment (MBI) is a syndrome that uses later‐life emergent and persistent neuropsychiatric symptoms (NPS) to identify a group at high risk for incident dementia. MBI is associated with neurodegenerative disease markers in advance of syndromic dementia. Functional connectivity (FC) correlates of MBI are understudied and could provide further insights into mechanisms early in the disease course. We used resting‐state functional magnetic resonance imaging (rs‐fMRI) to test the hypothesis that FC within the default mode network (DMN) and salience network (SN) of persons with MBI (MBI+) is reduced, relative to those without (MBI–). Methods From two harmonized dementia‐free cohort studies, using a score of ≥6 on the MBI Checklist to define MBI status, 32 MBI+ and 63 MBI– individuals were identified (mean age: 71.7 years; 54.7% female). Seed‐based connectivity analysis was implemented in each MBI group using the CONN fMRI toolbox (v20.b), with the posterior cingulate cortex (PCC) as the seed region within the DMN and anterior cingulate cortex (ACC) as the seed within the SN. The average time series from the PCC and ACC were used to determine FC with other regions within the DMN (medial prefrontal cortex, lateral inferior parietal cortex) and SN (anterior insula, supramarginal gyrus, rostral prefrontal cortex), respectively. Age, sex, years of education, and Montreal Cognitive Assessment scores were included as model covariates. The false discovery rate approach was used to correct for multiple comparisons, with a p‐value of .05 considered significant. Results For the DMN, MBI+ individuals exhibited reduced FC between the PCC and the medial prefrontal cortex, compared to MBI–. For the SN, MBI+ individuals exhibited reduced FC between the ACC and left anterior insula. Conclusion MBI in dementia‐free older adults is associated with reduced FC in networks known to be disrupted in dementia. Our results complement the evidence linking MBI with Alzheimer's disease biomarkers. Highlights Resting‐state functional magnetic resonance imaging was completed in 95 dementia‐free persons from FAVR and COMPASS‐ND studies. Participants were stratified by informant‐rated Mild Behavioral Impairment Checklist (MBI‐C) score, ≥6 for MBI+. MBI+ participants showed reduced functional connectivity (FC) within the default mode network and salience network. These FC changes are consistent with those seen in early‐stage Alzheimer's disease. MBI may help identify persons with early‐stage neurodegenerative disease.